Does Previous Perianal Surgery for Benign Diseases Have an Impact on Timing of Hospital Admission in Patients with Colorectal Cancer? - Sapmaz, Ali; Celik, Canbert; Kilic, Murat Ozgur; Bolukbasi, Hakan; Yilmaz, Serhan (Lietuvos chirurgija, 2023)
Objective. Colorectal cancer (CRC) is one of the most common and fatal malignancies worldwide. Although the clinical presentation varies according to the location of the tumor, hematochezia, tenesmus, changes in the defecation habit, chronic constipation, abdominal pain, and distension are the most common findings of CRCs. We aimed to investigate whether patients with CRC who had a surgical history for benign anal disease have more negative tumoral features or not. Material and Methods. Two-hundred fifty two patients who underwent surgery for CRC between 2010 and 2016 at general surgery clinic in Ankara Numune Training and Research Hospital included in this study. Patients were classified into two groups; patients who had undergone surgery for benign perianal disease such as hemorrhoid, anal fissure, perianal abscess and fistulae (Group 1) and patients without past history for perianal surgery (Group 2). Results. A total of 252 CRC patients with a mean age of 64.2 years were included in the study. There were 95 (37.7%) females and 157 (62.3%) males. There were 25 (9.9%) patients who had surgical history for benign perianal disease. There were no statistically differences in tumor size, lymph node positivity, presence of distant metastasis, and tumor stage between the groups (p > 0.05). Conclusion. Although not statistically significant, CRC patients with a history of surgery for benign perianal disease had less lymphatic metastases and tumor size than those without prior perianal surgery. We think that this finding is important in that it indicates the importance of detailed and appropriate evaluation of patients with CRC.